Spray form Solarsept vs. diluted sodium hypochlorite for the disinfection of alginate impressions - Katalbas, Fidel Jacob I.; Ong, Justin Ronald B.; De Castro, Elizabeth G. (Adviser).
INTRODUCTION: Alginate is an impression material that is prone to dimensional changes; therefore it is recommended to pour the stone as soon as possible when using this material. Unsurprisingly, due to time constraint, disinfection of this material could frequently be overlooked and rinsing the impression under running water is all that is done. Spray disinfection is a convenient disinfection method that requires minimal time and effort to perform, thus the objective of this study is to determine the effectiveness of two sprayed disinfectants, spray form Solarsept and diluted sodium hypochlorite (1:10), in reducing microbial load of alginate impressions under the time when alginate supposedly changes in dimension.
METHODS: In this experiment, 16 participants were recruited. Three mucostatic impressions of the maxillary arch were taken with one week intervals. Pre and post disinfection swabs were collected from three sites of the impression. The disinfectants used were diluted sodium hypochlorite, Solarsept, and water as a control. The collected samples were swabbed on blood agar plates and then incubated for 48 hours under the temperature of 37 degrees Celsius. Colonies of haemolytic bacteria were manually counted.
RESULTS: Diluted sodium hypochlorite was able to reduce bacterial load in samples by more than 98% after 2 minutes and 100% after 5 minutes. Solarsept, on the other hand, produced results of effectiveness with 66.02% reduction of bacterial colonies after 2 minutes and 100% of bacterial colonies in 5 minutes.
CONCLUSION: Based on the analysis of the results, diluted sodium hypochlorite is effective in disinfecting alginate impressions and is able to reduce 99.81% of bacterial colonies in 2 minutes and 100% of bacterial colonies in 5 minutes.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Sodium hypochlorite; Dental impressions; Alginates; Solarsept